FACTORS INFLUENCING INFORMATION SEEKING BEHAVIOUR OF AQUACULTURE EXTENSION PERSONNELS - ALAGAPPAN, M.; KUMARAN, M. (Journal of the Inland Fisheries Society of India, 2021)
The present study is designed to examine the information seeking behaviour of aquaculture extension personnel in India. A structured questionnaire was used to collect data from 120 aquaculture extension personnel comprising 60 each in public and private sectors. The results indicate that the respective parent organization was the main source of information for extension personnel in both the sectors. Majority of the public extension personnel felt lack of time as major constraint to seek information, as they were more focused on administrative, regulatory and welfare measures. In case of private extension personnel, lack of time, inadequate linkage with research institutions and non-relevancy of research publications to field problems were major constraints in seeking information. Inadequate manpower, funds, poor transport facility to visit farmers and more work in administration, regulation and welfare measures were the major constraints for information dissemination by the public extension personnel. While, lack of motivation, poor information flow from research to extension, lack of feedback and non availability of suitable technology were major constraints for information dissemination by the private extension personnel. The study has revealed that the aquaculture extension system lacked regular linkage with research institutions for capacity building.Key words: Aquaculture extension, extension personnel, information source, information dissemination, constraints